2011
DOI: 10.1016/j.scitotenv.2011.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal and pesticide content in commonly prescribed individual raw Chinese Herbal Medicines

Abstract: Heavy metal and pesticide contamination has previously been reported in Chinese Herbal Medicines (CHMs), in some cases at potentially toxic levels. This study was conducted to determine general patterns and toxicological significance of heavy metal and pesticide contamination in a broad sample of raw CHMs. Three-hundred-thirty-four samples representing 126 species of CHMs were collected throughout China and examined for arsenic, cadmium, chromium, lead, and mercury. Of the total, 294 samples representing 112 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(94 citation statements)
references
References 39 publications
(51 reference statements)
4
83
1
6
Order By: Relevance
“…Harris, et al27 collaborated with Chinese investigators to conduct federally funded research to analyze heavy metals and pesticides in commonly prescribed raw herbs from a wide range of geographical areas in China. In this study, 334 samples of raw herbs (representing 126 individual species) were collected and examined in duplicate for arsenic, cadmium, chromium, lead, and mercury.…”
Section: Discussionmentioning
confidence: 99%
“…Harris, et al27 collaborated with Chinese investigators to conduct federally funded research to analyze heavy metals and pesticides in commonly prescribed raw herbs from a wide range of geographical areas in China. In this study, 334 samples of raw herbs (representing 126 individual species) were collected and examined in duplicate for arsenic, cadmium, chromium, lead, and mercury.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of undeclared toxic metals in Asian products, especially natural products used in Indian Ayurveda medicine and of Chinese origin is widely reported [46][47][48]. Sahoo, Manchikanti, and Dey [49], pointed high frequency of the metals Fe, Pb, Hg, Cu, Cd, Zn, and As in Asian products.…”
Section: Resultsmentioning
confidence: 99%
“…This study found that pesticides were detectable in 36.7% of samples and at least one metal was found in all samples. 6 The poorly regulated nature of this industry makes it likely that alternative treatments could contribute to otherwise unexplained eosinophilia. A prior study had found that up to 70% of patients who use unconventional therapies did not inform their medical doctor, which reinforces the need to take a thorough history when evaluating patient eosinophilia.…”
Section: Discussionmentioning
confidence: 99%